Long-Term Effects of Placental Growth on Overweight and Body Composition - Johan G. Eriksson; Jill Gelow; Kent L. Thornburg; Clive Osmond; Markku Laakso; Matti Uusitupa; Virpi Lindi; Eero Kajantie; David J. P. Barker (Hindawi Limited, 2012)
Obesity is programmed in utero and small babies generally have small placentas. In some circumstances, an undernourished fetus can expand its placental surface to extract more nutrients. We hypothesize that this results in an imbalanced nutrient supply to the fetus leading to obesity. To determine whether placental size determines overweight and body composition, we studied 2003 subjects in adult life. Associations between placental surface area and indices of overweight were restricted to people who carried the Pro12Pro genotype of the PPARγ2 gene. For every 1 SD increase in placental surface area, the odds ratio for overweight was 1.37 (95% CI 1.10 to 1.71; P=0.005). Expansion of the placental surface in compensation for fetal undernutrition increases the risk of overweight and a higher body fat percentage in people carrying the Pro12Pro genotype. We suggest that similar underlying multifactorial mechanisms affect the development of obesity in general.